2016
DOI: 10.3928/01477447-20160419-04
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Antiplatelet Use Associated With Increased Blood Loss in Lumbar Spinal Surgery Despite Adherence to Protocols

Abstract: There are conflicting reports regarding postoperative bleeding risks associated with discontinuation of antiplatelet therapy at least 7 days preoperatively. Most of the studies in the spine literature are based on surveys or anecdotal evidence. The majority of surgeons discontinue therapy 7 days preoperatively, but this varies widely from 5 to 21 days. The purpose of this retrospective study was to assess whether chronic antiplatelet use is associated with increased intraoperative blood loss, need for transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The greater use of medications interfering with coagulation or platelet function in aged people with comorbidities has been hypothesized as an additional explanation [ 24 , 25 ]. Indeed, our data confirmed past research that suggested such treatments significantly increased the risk of bleeding, either intraoperatively and/or from postoperative blood drainages, in patients undergoing lumbar fusion, despite discontinuation of therapy at least 1 week preoperatively [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…The greater use of medications interfering with coagulation or platelet function in aged people with comorbidities has been hypothesized as an additional explanation [ 24 , 25 ]. Indeed, our data confirmed past research that suggested such treatments significantly increased the risk of bleeding, either intraoperatively and/or from postoperative blood drainages, in patients undergoing lumbar fusion, despite discontinuation of therapy at least 1 week preoperatively [ 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 88%
“…McCunniff et al 28 performed a retrospective analysis in patients undergoing elective lumbar surgery, excluding known hypercoagulable states (eg, malignancy) or coagulopathies (eg, on warfarin). All patients stopped antiplatelet agents 7 days prior to surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, clopidogrel had 444.39 ± 239.42 versus 447.83 ± 312.06 cm 3 per level of fusion blood loss and 447.88 ±249.97 versus 512.77 ± 332.66 cm 3 per level of instrumentation blood loss ( P < .01). 28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations